A revision of the endemic Hawaiian genus Thyrocopa (Lepidoptera: Xyloryctidae: Xyloryctinae) - Medeiros, Matthew J. (Zootaxa, 2009)
The endemic Hawaiian moth genus Thyrocopa (Xyloryctidae: Xyloryctinae) is revised. Thirty-one species are recognized, including seven new species: apikia sp. n., elikapekae sp. n., kanaloa sp. n., kea sp. n., kokeensis sp. n., neckerensis sp. n., and nihoa sp. n. The following new synonymies are proposed: T. depressariella Walsingham, T. fraudulentella Walsingham, T. immutata Walsingham, T. ingeminata Walsingham, T. nubifer Walsingham, and T. pallida Walsingham as junior synonyms of T. abusa Walsingham; T. adumbrata Walsingham and T. inermis Walsingham as junior synonyms of T. alterna Walsingham; T. mediomaculata Walsingham as a junior synonym of T. apatela (Walsingham); T. phycidiformis (Walsingham) as a junior synonym of T. brevipalpis (Walsingham); T. pulverulenta Walsingham as a junior synonym of T. epicapna (Meyrick); T. argentea (Butler) and T. tessellatella Walsingham as junior synonyms of T. indecora (Butler); and T. criminosa Meyrick, T. librodes Meyrick, and T. sucosa Meyrick as junior synonyms of T. usitata (Butler). A lectotype is designated for T. megas.